Kajian Visual Lambang Keraton Yogyakarta - Dwi Haryanto (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2023)
The emblem of the Yogyakarta Palace in the field of visual communication design is a form of visual identity logo that represents the ideal of an institutional entity that reflects the cultural image, perspective, and specific goals, which is rich in sign and meaning. The purpose of the research is to explore the meaning and visual patterns contained in the emblem of the Yogyakarta Palace in this study using an iconography and iconology approach that emphasizes the study of meaning in the visual elements of the visual object of the emblem of the Yogyakarta Palace, described by descriptive qualitative methods. The results of the study found the concept of Javanese culture that is typical in the aspect of its visual meaning. The concept of Manunggaling Kawula Gusti is interpreted as unity, national spirit, namely Loro-loroning Atunggal which is then realized in two symbols, namely Praja Cihna Cihnaning Nagari and Praja Cihna Cihnaning Salira Pribadi. The visual elements in it show the influence of classical Javanese culture (Hindu and Buddhist era), and European aesthetic concepts of the colonial era that are aligned with Islamic values, where to show their distinctive identity, they have changed into the elements of Javanese iconography, describing the concept of nationalism, besides as a form of personal actualization, but further to show their identity as a nation.